The Role of Atopy in the Choroidal Profile of Keratoconus Patients - Moleiro, Ana Filipa (Clin Ophthalmol, 2021)
PURPOSE: Although classically classified as a non-inflammatory condition, an inflammatory basis for keratoconus (KC) appears to be a growing evidence. Recently, it has been shown that KC patients have an increased choroidal thickness (CT). Among inflammatory disorders, atopy has been associated with KC development; therefore, the aim of this study was to evaluate if the increased CT in patients with KC is related to atopy. METHODS: This is an analytical cross-sectional study of patients with KC. Patients were classified as atopic and non-atopic according to their atopy history (allergic rhinoconjunctivitis (AR), asthma (AA) and/or atopic dermatitis (AD)) and were also classified based on their eye rubbing habits. Choroidal profile of all subjects was evaluated using a Spectralis optical coherence tomography (OCT) device with enhanced depth imaging (EDI) mode. CT was measured and compared between groups at the center of the fovea and at 500 µm intervals along a horizontal section. A multivariable analysis, adjusted for sex, age, spherical equivalent, history of medication and atopy, was performed to assess the influence of atopy in CT. RESULTS: Of the 80 patients included, 51 were atopic and 29 non-atopic. Atopic patients showed a thicker choroid in every measured location than the non-atopic patients (mean subfoveal CT 391.53 µm vs 351.17 µm, respectively), although the differences were not statistically different. The multivariable analysis revealed that being atopic makes the choroid statistically thicker, on average, 55.14 µm, when compared to non-atopic patients (p=0.043). Furthermore, patients who are frequent eye rubbers have significantly thicker choroids than non-rubbers (p=0.004). CONCLUSION: Although some results do not reach statistical significance, atopic KC patients seem to have thicker choroids compared with non-atopic KC patients, suggesting a possible role for atopy in the choroidal profile of KC. This constitutes a completely new sight in this field of research that needs further investigation.